Pengaruh ketebalan dan kombinasi jenis filter terhadap nilai Entrance Skin Exposure (ESE) menggunakan factor eksposi pemeriksaan kepala - Salimatul Litasova; Eko Hidayanto; Muchammad Azam (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Research on the analysis of the effect of filter type variation and thickness on mobile X-ray machine against ESE value of head examination. The use of filters aims to eliminate the low-energy X-ray beam so as to minimize the dose. The experiment was conducted to determine the ESE value and the thickness of the beak (HVL) on the combination of type and thickness of the filter. Combination filter used was aluminum (Al) with copper (Cu), aluminum with zinc (Zn), aluminum with galvalum (AlZnSi), aluminum (Al)), copper (Cu) with galvalum (AlZnSi), copper (Cu) with zinc (Zn), stainless steel (SS) with galvalum (AlZnSi) and stainless steel (SS) with zinc (Zn) ). With variation of 70, 81 and 90 kV fixed-time line voltages 20 mAs, 100 cm SSD, and 10 x 10 cm irradiation field measured tube voltage and ESE with combination of type and thickness of the filter. The results showed that ESE value with head examination exposure factor using combination of 1-1,5 mm filter Al with Zn, and combination of 1.5 mm filter Al with galvalum was at tolerance 0,348 - 0,522 mGy. While the exposure factor with combination of filter, Cu with Zn, Cu with galvalum, Cu with Al, SS with Al, SS with Zn and SS with galvalum with thickness of filter combination 1-2 mm under tolerance limit. So that can be used alternative materials other than filter Al can use combination of filter SS with AlZnSi. Half-Value Layer (HVL) exposure factor 90 kV with an filter Al with galvalum, we can use a 0.52 mm filter on a 0.71 mm filter Al with Zn. Keywords: x-ray machine, ESE, filter, HVL